Critical Legal Studies: The Omnibus Law Method In the Formulation of Local Regulations on Local Taxes and Levies - Taufiq Ismail; Uu Nurul Huda; Dedi Mulyadi (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2025)
This article examines the application of the Omnibus Law method in the formation of Regional Regulations on Taxes and Levies in Cianjur Regency through the lens of Critical Legal Studies (CLS). CLS, as a school of critical legal thought, challenges the assumption that law is neutral and objective and critically examines its relationship to political and economic power. This study aims to analyse the mechanism for drafting regional regulations using the Omnibus Law method and to assess the legal implications of its application in the absence of a clear technical framework. The research employs a normative approach, with conceptual and historical analyses of national regulations, particularly Law Number 12 of 2011 and its amendments, as well as case studies in Cianjur Regency. The findings indicate that, although the Omnibus Law has been codified in Law Number 13 of 2022, there are still insufficient technical regulations governing the formation of regional legal products under the Omnibus framework. This creates the risk of formal defects in the establishment of regional rules, potentially undermining their legal validity. Therefore, the application of the Omnibus Law method at the regional level requires careful study, and the principles of CLS can serve as a critical analytical tool for evaluating legislative processes heavily influenced by political and economic interests.